"The Lumber Piles Must Go": Ottawa's Lumber Interests and the Great Fire of 1900 - Fear, Jon (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1979)
Ottawa's great fire of 1900 destroyed much of a lumber manufacturing and working class area. The conflagration also revealed a set of tensions that pitted public safety against both the workers' need for cheap homes, safe from fire, and industry's needs for piling grounds for lumber. Politicians and the public agonized at length over the problem, but they achieved only deadlock and changed nothing.